Empowering Ciung Wanara Tourism Site Food Stall Owners with Digital Marketing Expertise and Business Licencing - Saefullah , Aep; Fahri, Fahri; Hidayatullah , Syarif (Universitas Ahmad Dahlan, 2023)
Background: In the neighborhood of Ciung Wanara tourist area in the Ciamis district, 25 food stall owners have been selling for more than 10 years. They trade manually without having good entrepreneurial skills, do not use digital technology in marketing products, and do not have a formal business license. Contribution: This activity aims to provide understanding and knowledge of food stall owners about digital marketing and strengthen business legality permits. Method: The method applied uses a pattern of observation, training, socialization, direct face-to-face discussion (offline), as well as the direct practice of creating social media accounts and making business legality permits. Results: The output of this service produces two aspects for shop owners. First, in the digital marketing aspect, business actors already have social media accounts including Google business, Facebook marketplace, Instagram, and WhatsApp business. In addition, they can understand and operate these social media tools for their business activities. Second, the formal legal aspects of the business. Business actors already have a business license in the form of a firm recognition Number (NIB). Conclusion: This activity is very beneficial directly for business actors. Having social media can increase sales turnover. And having NIB, they can develop their business, support the security and comfort of doing business and get legal certainty in enterprises.